The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/03635465221079858
|View full text |Cite
|
Sign up to set email alerts
|

Primary Open Latarjet Procedure Results in Functional Differences but No Structural Changes in Subscapularis Muscle Quality vs the Healthy Contralateral Shoulder at Long-term Follow-up

Abstract: Background: There are concerns that the Latarjet procedure results in loss of glenohumeral rotation and strength and in subscapularis dysfunction. The long-term effects of this procedure on subscapularis quality, glenohumeral rotation, and strength are unknown. Purpose/Hypothesis: To analyze the long-term effect of the primary open Latarjet procedure using a muscle-splitting approach on internal and external rotation and strength, as well as subscapularis muscle quality as compared with the healthy contralater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
10
2
Order By: Relevance
“…6 However, Ernstbrunner et al reported reduced strength in internal and external rotation of the shoulder after open Latarjet surgery. 7 In a sample of 20 patients, Malavolta et al similarly evaluated shoulder and elbow strength after open Latarjet surgery, however, they reported reduced strength of external rotation and forearm supination, findings that differ from ours. 8 In a sample of 20 patients undergoing open Latarjet surgery, Lacheta et al reported reduced forearm supination strength but did not affect elbow flexion at a mean follow up of 9.8 months.…”
Section: Caubere Et Al Described a Series Of 20 Patients After Opencontrasting
confidence: 67%
“…6 However, Ernstbrunner et al reported reduced strength in internal and external rotation of the shoulder after open Latarjet surgery. 7 In a sample of 20 patients, Malavolta et al similarly evaluated shoulder and elbow strength after open Latarjet surgery, however, they reported reduced strength of external rotation and forearm supination, findings that differ from ours. 8 In a sample of 20 patients undergoing open Latarjet surgery, Lacheta et al reported reduced forearm supination strength but did not affect elbow flexion at a mean follow up of 9.8 months.…”
Section: Caubere Et Al Described a Series Of 20 Patients After Opencontrasting
confidence: 67%
“…43 A simulated Latarjet procedure was then performed in these 2 different bone loss conditions under the 3 humeral head configurations. The distal 25 mm of the coracoid process was cut and transferred to the anteroinferior region of the glenoid 22,49 so that the bone graft was flush with the glenoid bone (mediolateral direction) and approximately 75% of the graft surface was below the glenoid equator of the inferior two-thirds of the glenoid height (craniocaudal direction). 42 Then, two 4.5-mm cortical screws separated by 10 mm were positioned at an angle of 10°to the glenoid plane 10 to secure the graft to the glenoid neck.…”
Section: Simulationsmentioning
confidence: 99%
“…It provides a triple blocking effect to increase anterior shoulder stability, and this has been well described in the literature. [1][2][3][4][5][6] Although the indications vary from surgeon to surgeon, we typically consider Latarjet for high-risk patients for recurrent instability who have any glenoid bone loss or low-risk patients who have between 15% and 30% anterior glenoid bone loss. 3,7 For those lower risk patients with \15% glenoid bone loss, we typically perform an Surgical Techniques arthroscopic stabilization procedure.…”
Section: Video Transcriptmentioning
confidence: 99%
“…It provides a triple blocking effect to increase anterior shoulder stability, and this has been well described in the literature. 1-6…”
Section: Video Transcriptmentioning
confidence: 99%